2017
DOI: 10.1080/23802359.2017.1303343
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Cerion uva uva (Gastropoda: Panpulmonata: Stylommatophora: Cerionidae)

Abstract: We report the complete mitochondrial genome sequence of Cerion uva uva (Linnaeus 1758), the type species of the type genus of the family Cerionidae. The mitogenome is 15,043 bp in length, has a base composition of A (28.3%), T (34.4%), C (17.3%) and G (20.0%), and contains 13 protein-coding genes, 2 ribosomal RNA genes, as well as 22 transfer RNA genes. Gene order is the same as in Cerion incanum (Leidy 1851), but differs from those of all other Panpulmonata. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Colours for the families as in Fig. 2: light blue -Hygromiidae; green -Geomitridae; brown -Polygyridae; red -Helicidae; dark blue -Camaenidae two clades i.e., Bradybaeninae and Camaeninae, treated frequently as two separate families (Lin et al 2016;Minton et al 2016a;Harasewych et al 2017). Our results agree with the division of Helicidae and Camaenidae into subfamilies (Bouchet at al.…”
Section: Start Codons Stop Codonssupporting
confidence: 86%
See 1 more Smart Citation
“…Colours for the families as in Fig. 2: light blue -Hygromiidae; green -Geomitridae; brown -Polygyridae; red -Helicidae; dark blue -Camaenidae two clades i.e., Bradybaeninae and Camaeninae, treated frequently as two separate families (Lin et al 2016;Minton et al 2016a;Harasewych et al 2017). Our results agree with the division of Helicidae and Camaenidae into subfamilies (Bouchet at al.…”
Section: Start Codons Stop Codonssupporting
confidence: 86%
“…Phylogenetic analyses of the stylommatophoran mitogenomes (González et al 2016;Romero et al 2016) showed them in a well-supported clade among Panpulmonata (with PP and bootstrap values 1 and 99, respectively). Previous mitogenome phylogenies of stylommatophoran superfamilies (Groenenberg et al 2017;Harasewych et al 2017;Yang et al 2019;Doğan et al 2020) showed a clade of Helicoidea separate from other superfamilies, although mitogenomes of only 11 stylommatophoran superfamilies (Yang et al 2019) out of 26 listed by Bouchet et al (2017) are represented in GenBank. According to Bouchet et al (2017), Helicoidea includes 17 families but hitherto phylogenetic relationships could be analysed only for three or four of them, namely Helicidae, Camaenidae, Geomitridae, and Polygyridae (González et al 2016;Lin et al 2016;Minton et al 2016a;Harasewych et al 2017;Doğan et al 2020).…”
Section: Resultsmentioning
confidence: 99%